Assessment of Disease Activity in Large-vessel Vasculitis: Results of an International Delphi Exercise - DİRESKENELİ, RAFİ HANER (My University, 2017)
Objective. To arrive at consensus for candidate outcomes for disease activity assessment in large-vessel vasculitis (LVV) in clinical trials. Methods. A Delphi survey including 99 items was circulated among international experts for 3 rounds. Results. Fifty-seven items were accepted for both giant cell arteritis and Takayasu arteritis. Sixty-seven percent of experts voted to have a common approach for both diseases with additional disease-specific items such as weight loss, scalp tenderness/necrosis, morning stiffness, dizziness, visual symptoms, and imaging. Conclusion. This study highlights similarities and differences in experts’ perspectives for assessing clinical activity in LVV and may guide a consensus-driven core set of validated outcomes.
Assessment of Disease Activity in Large-vessel Vasculitis